Association between circadian genes, bipolar disorders and chronotypes. (August 2014) - Etain, B.; Jamain, S.; Milhiet, V.; Lajnef, M.; Boudebesse, C.; Dumaine, A.; Mathieu, F.; Gombert, A.; Ledudal, K.; Gard, S.; Kahn, J. P.; Henry, C.; et al.
<x xml:space="preserve">Abstract</x> Abnormalities in circadian rhythms play an important role in the pathogenesis of bipolar disorders (BD). Previous genetic studies have reported discrepant results regarding associations between circadian genes and susceptibility to BD. Furthermore, plausible behavioral consequences of at-risk variants remain unclear since there is a paucity of correlates with phenotypic biomarkers such as chronotypes. Here, we combined association studies with a genotype/phenotype correlation in order to determine which circadian genes variants may be associated with the circadian phenotypes observed in patients with BD. First, we compared the allele frequencies of 353 single nucleotide polymorphisms spanning 21 circadian genes in two independent samples of patients with BD and controls. The meta-analysis combining both samples showed a significant association between rs774045 in TIMELESS (OR = 1.49 95%CI[1.18–1.88]; p = 0.0008) and rs782931 in RORA (OR = 1.31 95%CI[1.12–1.54]; p = 0.0006) and BD. Then we used a "reverse phenotyping approach" to look for association between these two polymorphisms and circadian phenotypes in a subsample of patients and controls. We found that rs774045 was associated with eveningness (p = 0.04) and languid circadian type (p = 0.01), whereas rs782931 was associated with rigid circadian type (p = 0.01). Altogether, these findings suggest that these variants in the TIMELESS and RORA genes may confer susceptibility to BD and impact on circadian phenotypes in carriers who thus had lower ability to properly adapt to external cues.